2008
DOI: 10.1128/jb.00630-08
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of the Role of RNase R in the Turnover of Pseudomonas putida mRNAs

Abstract: RNase R is a 3-5 highly processive exoribonuclease that can digest RNAs with extensive secondary structure. We analyzed the global effect of eliminating RNase R on the Pseudomonas putida transcriptome and the expression of the rnr gene under diverse conditions. The absence of RNase R led to increased levels of many mRNAs, indicating that it plays an important role in mRNA turnover.Attaining a proper balance between mRNA synthesis and degradation is essential for determining levels of gene expression. The degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…The Tn903dIIlacZ insertion has been mapped at nucleotide (nt) 513 of the RNase R coding sequence and does not produce a translational fusion with lacZ. Since RNase R has been reported for several species to be required for growth at low temperatures (5,16,17,26), we analyzed the growth of an L. pneumophila rnr strain under axenic conditions on solid rich medium at optimal and suboptimal growth temperatures. The RNase R mutant did not show significant growth defects at optimal (37°C) or elevated (42°C) growth temperatures (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Tn903dIIlacZ insertion has been mapped at nucleotide (nt) 513 of the RNase R coding sequence and does not produce a translational fusion with lacZ. Since RNase R has been reported for several species to be required for growth at low temperatures (5,16,17,26), we analyzed the growth of an L. pneumophila rnr strain under axenic conditions on solid rich medium at optimal and suboptimal growth temperatures. The RNase R mutant did not show significant growth defects at optimal (37°C) or elevated (42°C) growth temperatures (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, we found that the comEA mRNA has a longer half-life in the rnr mutant, indicating that it is a substrate of RNase R. Indeed, the sole inactivation of the exoribonuclease activity of RNase R at 30°C is sufficient to induce competence development. A recent genome-wide analysis of mRNA decay in an rnr mutant of Pseudomonas putida has revealed the important role of RNase R in mRNA turnover (17). Although RNase R is active on mRNAs containing REP sequences, the mRNAs affected by the lack of RNase R were not enriched in REPcontaining sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To partially validate the trends of the microarray results, quantitative reverse transcription-PCR (qRT-PCR) was performed on isolated RNA (obtained from a batch of [P]PSMs separate from the ones used for the microarray) for selected genes (algT, alg8, mucA, fliE, and flgM) with 3 replicates for each condition (4 h, 72 h, and control). The primer sets (13,22) are listed in Table S3 in the supplemental material. cDNA synthesis and amplification were performed using the Qscript 1-Step Sybr green qRT-PCR kit (Quanta Biosciences, Maryland) in a Chromo4 thermocycler (MJ Research, Massachusetts) with a total RNA input of 50 ng according to the standard protocol of the manufacturer (Quanta Biosciences, Maryland).…”
Section: Methodsmentioning
confidence: 99%
“…Inactivation of rnr has been found to result in elevated levels and/or half-lives of over 100 transcripts in Pseudomonas putida (16). It is thus possible that rsmY degradation may be dependent on exoribonuclease RNase R under biofilm growth conditions.…”
mentioning
confidence: 99%